HUBUNGAN PENGETAHUAN IBU BALITA DENGAN MOTIVASI MEMBERI MAKANAN BERGIZI DI DESA PANAONGAN KECAMATAN PASONGSONGAN - Iva Gamar Dian Pratiwi; Nur Azifa (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2017)
The National Target stipulates that the coverage target of underweight children weighs in the weighted appeal of 80% but in fact the coverage of underweight who weighs in the appeal weighed in Panongan Village is 56.91% of the 80% target in 2014. The purpose of this study is to know the relationship of knowledge with the mother's motivation in providing nutritious food. The research method used is analytic and research design that used is cross secsional, population in this research is all mother having toddler with amount of 298 people and taken sample171 people. By using stratified proportional random sampling technique, independent variable of mother's knowledge, dependent variable of mother's motivation in giving nutritious food, collecting data used in the form of questionnaire and using spearman test with degree of significance α = 0,05. The results showed that almost half (49.8%) ie 85 people have less knowledge and almost half (49.8%) of 85 people have a weak motivation. The result of spearman test analysis shows the value (ρ) = 0.000 and (α) = 0,05 thus ρ <α so Hо rejected means there is relation between knowledge with mother motivation in giving nutritious food. It is hoped that health workers will increase the extension to mothers so that the mother's knowledge will increase and the mother's motivation to have the toddler gives higher nutritious food to improve the good growth for her toddler.